2009
DOI: 10.1245/s10434-008-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Melphalan Pharmacokinetics in Regional Melanoma Therapy: Does Correcting for Ideal Body Weight Alter Regional Response or Toxicity?

Abstract: Background This study aims to determine what effect correcting melphalan dosing for ideal body weight (IBW) has on toxicity and response in isolated limb infusion (ILI) in patients with advanced extremity melanoma. Methods This was an open observational study examining whether correcting the melphalan dose for IBW will influence response and toxicity in patients undergoing ILI for advanced extremity melanoma in 41 patients undergoing 42 procedures (13 without correction for IBW; and 29 with correction for IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…7 Limb volume was calculated by integrating extremity circumference at 1.5-cm intervals up to the level of tourniquet placement, and chemotherapy dosing was corrected for ideal body weight on the basis of evidence that such modification reduces severe toxicity without altering CR rates. 20 Some patients were also enrolled onto phase I/II clinical trials combining ILI with a systemic targeted agent: 19 patients received 14 days of sorafenib with ILI occurring on day 7, while 30 patients received ADH-1 at least 4 hours before ILI and on postoperative day 7. 21,22 The melphalan concentration in plasma from the infusion circuit was measured at 5, 10, 15, 20, 25, and 30 minutes by an improved assay based on a published high-performance liquid chromatography–fluorescence method by Ehrsson et al 23 …”
Section: Methodsmentioning
confidence: 99%
“…7 Limb volume was calculated by integrating extremity circumference at 1.5-cm intervals up to the level of tourniquet placement, and chemotherapy dosing was corrected for ideal body weight on the basis of evidence that such modification reduces severe toxicity without altering CR rates. 20 Some patients were also enrolled onto phase I/II clinical trials combining ILI with a systemic targeted agent: 19 patients received 14 days of sorafenib with ILI occurring on day 7, while 30 patients received ADH-1 at least 4 hours before ILI and on postoperative day 7. 21,22 The melphalan concentration in plasma from the infusion circuit was measured at 5, 10, 15, 20, 25, and 30 minutes by an improved assay based on a published high-performance liquid chromatography–fluorescence method by Ehrsson et al 23 …”
Section: Methodsmentioning
confidence: 99%
“…If the hand or foot of the involved extremity is free of disease, a second optional esmarch or pneumatic tourniquet may be used to exclude these areas from the circuit. In this situation, the hand or foot volume should be subtracted from the total limb volume 50. Some groups, including our own, now correct melphalan dosing for ideal body weight based on evidence that this dose modification is associated with lower toxicity without altering the complete response rate 50…”
Section: Melphalanmentioning
confidence: 99%
“…It was therefore postulated that melphalan dosing was excessive in patients with a high total to lean body weight ratio as preferential distribution of melphalan was resulting in excessively high muscle levels. Correction of melphalan dose for ideal body weight (IBW) has been shown to substantially decrease the rate of compartment syndrome, the incidence of grade 3 regional toxicity scores and peak CK value [31]. A recent multi-centre review found that correction of melphalan dose for IBW did confirm a marked reduction in toxicity (p<0.001).…”
Section: Melphalan Dosingmentioning
confidence: 99%